Immunological homeostasis and immune diseases of liver - V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. To present mechanisms of regulation of liver immunological homeostasis and pathological reactions causing autoimmune diseases.Original positions. Predisposition to autoimmune hepatitis is determined by carriage of HLA-DR B1*0301 or HLA-DR B1*0401 alleles. Patients with autoimmune hepatitis receiving no treatment and relapse phase of disease have deficiency or the functional failure of CD4+ CD25+ regulatory Т-cells. Th1-cells induce expression of HLA class I molecules on hepatocytes that increases sensibility of hepatocytes to attacks of cytotoxic CD8+ Т-cells. Th2-cells induce autoantibodies production by B-lymphocytes. Th17-cells are involved in development of inflammation and autoimmune reactivity. Congenital or acquired defects of expression of MDR3/ABCB4, CFTR, AE2/SLC4A2, genes that encode proteins of various transport systems of bile duct and tubule epithelium can take part in pathogenesis of primary biliary cirrhosis and primary sclerosing cholangitis. These genetic changes are accompanied by disorders of hydration, alkalinisation and colloidisation of bile, biliary thrombosis of tubules, inflammatory Т-cellular infiltration, development of cholangiogenic fibrosis and cirrhosis. Nuclear factor NF-kB represents the molecular bond bridging inflammatory, immune, protective and metabolic reactions in the liver. It is one of the key factors of pathogenic mechanisms, resulting in development of non-alcoholic steatohepatitis and hepatocellular carcinoma.Conclusion. Understanding of mechanisms of autoimmune liver disease broadens diagnostic and clinical horizons of modern doctor and yields new medical methodology.